Perhitungan Harga Pokok Pesanan (Job Order Costing) Produk â€œBRKT Number Plate K56â€ Pada PT. Rachmat Perdana Adhimetal - Hermanto, Bambang (Wiga : Jurnal Penelitian Ilmu Ekonomi, 2016)
The purpose of this study was to obtain information about the cost element production, the methods used and to find out the problems that occur during the decisive calculation of the cost of production of products "BRKT Number Plate K56" .Its produced by PT. Rachmat Prime Adhimetal. The method used is a literature study (Library Research) and Field Study (Field Research). The collection of data directly to the field by using data collection techniques are Interview (Interview) and Observation (Observasion) directly to the PT. Rachmat Prime Adhimetal in Jakarta for the month of February 2016. The results show the elements of the production cost of Raw Material Costs Direct Costs Direct Labor, and Factory Overhead either charged or real. The method used in the calculation of the cost of production "BRKT Number Plate K56" at PT. Rachmat Prime using full costing method taking into account all the costs associated with production activities into the calculation of the cost of production as well as the companies charge Overhead Actual stroke of the amount generated in each process.